2016
DOI: 10.5812/ircmj.34449
|View full text |Cite
|
Sign up to set email alerts
|

Application of Autologous Platelet-Rich Plasma (PRP) on Wound Healing After Caesarean Section in High-Risk Patients

Abstract: BackgroundPlatelet-rich plasma (PRP) is a human plasma product enriched by platelets, growth factors, and fibrinogen with high hemostatic and healing properties.ObjectivesThe aim of this study was to evaluate the effect of autologous PRP on wound healing in high-risk women undergoing cesarean sections.Patients and MethodsIn this balanced, randomized, and controlled trial, 140 patients were admitted to Arash women’s hospital, Tehran, Iran from May of 2013 to November of 2014 for elective cesarean surgery. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
5
26
0
Order By: Relevance
“…The previous results came in agreement with the study of Tehranian et al [17] which was the first prospective, randomized controlled trial evaluating the efficacy of autologous PRP in cesarean section, and it has concluded that PRP has positive effects on wound healing and pain reduction in high-risk patients undergoing cesarean section.…”
Section: Discussionsupporting
confidence: 88%
“…The previous results came in agreement with the study of Tehranian et al [17] which was the first prospective, randomized controlled trial evaluating the efficacy of autologous PRP in cesarean section, and it has concluded that PRP has positive effects on wound healing and pain reduction in high-risk patients undergoing cesarean section.…”
Section: Discussionsupporting
confidence: 88%
“…These morbid events are seen most commonly among high risk patients like diabetic women either gestational or pregestational and especially if uncontrolled glucose level which related to poor tissue perfusion, and subsequent tissue hypoxia that render wound healing 11 PRP which a new intervention admitted to surgical activities few years ago has been tried in different gynecological and obstetric procedures attributed to the endogenous platelet activities that enhance wound healing and accelerate tissue regeneration by releasing different growth factors and at the same time enhance local immunity that fight infection and allowing better scar formation that healed by primary intention with better cosmetic appearance of the wound 12,13 this study is a prospective randomized study conducted at the department of obstetric and gynecology, faculty of medicine, Minya University, Egypt during the period between January 2017 to December 2017 where 120 diabetic patients undergoing elective CS were recruited and randomly divided into 2 groups, control group, and study group where PRP used subcutaneously before skin closure to enhance wound healing, lower incidence of wound infection and gapping and reduce the incidence of ugly scar formation. Our assessment tools were REEDA scoring system to detect local wound changes as redness, edema, ecchymosis, discharge and approximation of the wound which used at day 1, 7, and 30 postoperatively also pain response post operatively was assessed by VAS system at the same period of post-operative days, 1, 7 and 30 follow up of the scar formation by VSS system was also assessed at days 1, 7 and 30 respectively as regard REEDA scoring between both groups, our results showing that there is significant difference between study and control group, but at 1st day the wound of PRP group showing more redness, edema and oozing discharge than the control group with p value 0.0001, however in the next following days 7 and 30, the PRP showing higher significant difference with more improvement of the wound REEDA scaling than the control group with p value less than 0.0001., there were 12 cases of gabbed wound in group 1, 8 of them were managed conservatively while other 4 cases needed secondary sutures, however there was no cases of gabbing in group 2 (p.value, 0.0001) the same findings of VAS and VSS scoring systems showing higher significant difference between both group with more fine and clean wound in PRP group than control group and better pain tolerability in PRP group than the control group except for the 1st day of assessment as there was more inflammatory reactions in PRP group than the control group with more need for analgesia at that day these findings are matched with that of Tehranian et al, 14 who found better REEDA scoring in PRP group than control group but did not document any wound changes in PRP group in day one which may be due to mixed patients types in Tehranian study as they examined all high risk patients but our selection is restricted to diabetics only also our results are matched with those of Marwa et al, 15 who studied different activators of PRP on REEDA, VAS, VSS scoring and found that PRP in general showing better results with less scar formation and lower incidence of infection similar studies used PRP in different non obstetric surgical procedures and found significant difference when PRP used in comparison with the control [16][17][18] in contrast to our results some authors deny any positive effect of ...…”
Section: Discussionsupporting
confidence: 80%
“…There is a growing consensus for the positive effects of PRP as an adjuvant therapy to aid the healing of surgical wounds and injuries. In fact, the growth factors present in PRP are involved in every stage of wound healing [71][72][73] , and several reviews [74][75][76][77][78] , systematic reviews [79][80][81] , and clinical studies [82][83][84] have reported their involvement in enhanced soft-tissue healing outcomes. Our results did not show statistically significant differences in the SWAS scores between the groups because they both obtained the best possible score.…”
Section: Discussionmentioning
confidence: 99%